2014
DOI: 10.4236/asm.2014.43007
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, Types and Predictors of Contraception among Female In-School and Out-of-School Adolescents in Onitsha, Anambra State, Nigeria

Abstract: Introduction: The consequences of unsafe sex are suffered mostly by adolescent girls in Nigeria despite efforts to improve accessibility to the reproductive and sexual health of this group. This study elucidates the pattern of contraceptive use, the key socio-demographic factors, sexual beliefs and practices associated with its use amongst adolescent girls in Nnewi, Nigeria. Methods: It was a descriptive cross-sectional comparative study of in-school and out-of-school female adolescents. Data were collected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
(18 reference statements)
2
20
1
1
Order By: Relevance
“…We also found that the most common reasons for not using any contraceptive were fear of side effects and religious beliefs. Our findings differ from the study done in Nigeria where female adolescents were not using contraceptives due to inadequate money, fearing that the use of contraceptive would render them infertile, or for fear of losing their lovers 22 as also indicated in a study done in Bahir Dar University in Ethiopia which reported that the use of contraceptives, especially condoms, decreases sexual pleasure. 23 …”
Section: Discussioncontrasting
confidence: 99%
“…We also found that the most common reasons for not using any contraceptive were fear of side effects and religious beliefs. Our findings differ from the study done in Nigeria where female adolescents were not using contraceptives due to inadequate money, fearing that the use of contraceptive would render them infertile, or for fear of losing their lovers 22 as also indicated in a study done in Bahir Dar University in Ethiopia which reported that the use of contraceptives, especially condoms, decreases sexual pleasure. 23 …”
Section: Discussioncontrasting
confidence: 99%
“…Age, level of education, location, income, psychocultural and health system (p=<0.001) are signi cantly associated with the utilization of post abortion care, while income (p=0.02), psychocultural (p=0.00) and health system (p=0.00) are signi cantly associated with the utilization of services for the prevention and management of STI, HIV, and AIDS. Table 4 shows that socio-demographic factors of gender; male (AOR = 0.64; CI = 0.43-0.95), age; [17][18][19][20][21][22] (AOR = 0.23; CI = 0.14-0.38), and lower income; <1000 (AOR = 0.84; CI = 0.72-0.99) were signi cantly associated with lower odds of SRHS utilization, while tertiary education (AOR = 2.93; CI = 1.93-4.46) and living in school (AOR = 1.40; CI = 1.13-1.73), were signi cantly associated with higher odds of SRHS utilization. Similarly, psycho-cultural (AOR = 2.40; CI = 1.50-3.84) and health system factors (AOR = 7.47; CI = 4.66-12.01) were signi cantly associated with higher odds SRHS utilization.…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, almost half of studies that measured program impact on condom use found increased condom use with none of them finding decreased condom use [21,[24][25][26]. The proportion of effective programs in developing countries was similar to the proportion in the developed countries in both school and community settings, irrespective of gender and age of populations [21].…”
Section: Effect Of Hiv Education On Condom Usementioning
confidence: 99%
“…However, sexual risk behaviours were more difficult to change. A 'Sex and HIV Education Programs for Youth' study [25] revealed that the intervention effect of peer education at the individual level was significant. The students who received peer education had a significantly higher attitudewhich influences behaviour compared with those who were not targeted.…”
Section: Effect Of Peer-based Intervention Hiv Knowledge and Behavioumentioning
confidence: 99%